Development of spatiotemporal validation methods of an agent-based model of epithelial cells: analysis of a colony of keratinocytes. (22nd December 2008) - Pichardo-Almarza, Cesar; Smallwood, Rod; Billings, S.A.
In this paper an Agent-Based Model (ABM) to study Normal Human Keratinocytes (NHK) (tissue cells) is investigated. ABM are widely used for the simulation of systems from several domains (biology, economics, meteorology, etc.). In biology, ABM are useful for predicting the social behaviour of systems; in particular, they seem well adapted to model the behaviour of a cell population. These models exhibit probabilistic behaviour and the validation of simulation results is often a qualitative analysis by experts (biologists). The aim of this paper is to propose new variables and metrics for the development of quantitative methods to validate the model.